INVESTIGATING THE IMPACT OF JUSTICE AND TRUST ON THE RESILIENCE OF HUMAN RESOURCES AND THE MAINTENANCE AND SUSTAINABILITY OF HUMAN RESOURCES (CASE STUDY: EMPLOYEES OF THE GENERAL WATER DEPARTMENT OF MOTHNI PROVINCE, IRAQ) - Nabil Al-Ziyadi; Morteza Movaghar; Mohsen Alizadeh Thani (Scholar Express Journals, 2022)
Considering the increasing and rapid changes in social life and changing human needs, the issue of resilience and maintaining human resources is considered by experts and thinkers as one of the basic challenges and crises of today's organizations, so the purpose of this study is to investigate The effect of justice and trust on the resilience of human resources and the maintenance and stability of human resources. In terms of the purpose, the current research is in the category of applied research, and in terms of the method of gathering information, it is descriptive and correlational. The time horizon of this research was cross-sectional. The statistical population of this research is the employees of the General Water Department of Mothni province in Iraq. The measurement tools related to all 4 variables of this research are standard questionnaires that have content and construct validity and their reliability is confirmed. In general, 7 hypotheses were examined in this research. The results of the hypothesis test showed that justice has a positive and significant effect on human resource resilience, but it does not have a significant effect on human resource retention. Also, trust has a positive and significant effect on the resilience of human resources and the maintenance of human resources. In addition, there is a causal relationship between the dependent variables in such a way that human resource resilience has a positive and significant effect on human resource retention. In the investigation of mediation hypotheses, it was also found that the mediating variable of resilience mediates the effect of trust on the retention of human resources and the effect of justice on the retention of human resources.
Keywords: Organizational justice; organizational trust; resilience of human resources